Evaluation of the efficacy of polymeric antigen BLSOmp31 formulated in a new cage-like particle adjuvant (ISPA YOLK) administered by parenteral or mucosal routes against Brucella ovis in rams - Moran, Maria Celeste; Tammone Santos, Agostina; Dominguez, Paula; Moriones, Lucila; Nieto Farias, María Victoria; Maté, Laura; Garcia, Juan Agustin; Kuhn, Tobias; Paolicchi, Fernando; Fiorentino, María Andrea; Rodriguez, Marcelo Gaston; García, Jorge Pablo; et al. (Elsevier, 2026)
Brucella ovis (B. ovis) is the etiological agent of ram-contagious epididymitis, the leading cause of reproductive disorders in flocks worldwide. Although the attenuated B. melitensis Rev.1 strain gives heterologous protection against this pathogen, it has important disadvantages. Subunit vaccines could provide a safer alternative that considers the One Health approach. Polymeric BLSOmp31 was previously identified as a protective immunogen against this pathogen. In our previous work in BALB/c mice, we evaluated the performance of BLSOmp31 formulated in a new cage-like particle adjuvant called ISPA. In the present study, we administered BLSOmp31, which was formulated in a new low-cost variant of ISPA called ISPA YOLK (BLSOmp31/ISPA YOLK). This formulation was given to rams through both subcutaneous and ocular routes. We evaluated the systemic and mucosal immune responses and assessed its protective capacity against B. ovis. BLSOmp31/ISPA YOLK admin istered by both routes induced systemic and variable mucosal IgG and IgA antibody response, without inter ference in the serological diagnosis. Additionally, this formulation induced significant specific cellular immune responses and an increase in the relative expression levels of cytokine genes in peripheral blood mononuclear cells with a mixed Th1/Th2 profile. While this vaccine did not prevent experimental infection with B. ovis, parenterally immunized rams had fewer infected organs and less severe histopathological changes in repro ductive organs compared to animals vaccinated by ocular route and non-immunized rams. In contrast, this formulation, whether administered by SC or CONJ route could reduce the elimination of B. ovis through semen, and minimize the risk of spreading the infection.